Yoga and Cardiovascular Health Trial (YACHT): a UK-based randomised mechanistic study of a yoga intervention plus usual care versus usual care alone following an acute coronary event - Naveed Sattar; Ian Roberts; Sanjay Kinra; Paul Welsh; Therese Tillin; A Hughes; Kaushik Chattopadhyay; Shah Ebrahim; Claire Tuson; Barbara Sowa; Nishi Chaturvedi (BMJ Open)
Objective To determine the effects of yoga practice on subclinical cardiovascular measures, risk factors and neuro-endocrine pathways in patients undergoing cardiac rehabilitation (CR) following acute coronary events.Design 3-month, two-arm (yoga +usual care vs usual care alone) parallel randomised mechanistic study.Setting One general hospital and two primary care CR centres in London. Assessments were conducted at Imperial College London.Participants 80 participants, aged 35–80 years (68% men, 60% South Asian) referred to CR programmes 2012–2014.Intervention A certified yoga teacher conducted yoga classes which included exercises in stretching, breathing, healing imagery and deep relaxation. It was pre-specified that at least 18 yoga classes were attended for inclusion in analysis. Participants and partners in both groups were invited to attend weekly a 6- to 12-week local standard UK National Health Service CR programme.Main outcome measures (i) Estimated left ventricular filling pressure (E/e′), (ii) distance walked, fatigue and breathlessness in a 6 min walk test, (iii) blood pressure, heart rate and estimated peak VO2 following a 3 min step-test. Effects on the hypothalamus–pituitary–adrenal axis, autonomic function, body fat, blood lipids and glucose, stress and general health were also explored.Results 25 participants in the yoga + usual care group and 35 participants in the usual care group completed the study. Following the 3-month intervention period, E/e′ was not improved by yoga (E/e′: between-group difference: yoga minus usual care:−0.40 (−1.38, 0.58). Exercise testing and secondary outcomes also showed no benefits of yoga.Conclusions In this small UK-based randomised mechanistic study, with 60 completing participants (of whom 25 were in the yoga + usual care group), we found no discernible improvement associated with the addition of a structured 3-month yoga intervention to usual CR care in key cardiovascular and neuroendocrine measures shown to be responsive to yoga in previous mechanistic studies.Trial registration number NCT01597960; Pre-results.